Absence of MCJ/DnaJC15 promotes brown adipose tissue thermogenesis - Beatriz Cicuéndez; Alfonso Mora; Juan Antonio López; Andrea Curtabbi; Javier Pérez-García; Begoña Porteiro; Daniel Jimenez-Blasco; Pedro Latorre-Muro; Paula Vo; Madison Jerome; Beatriz Gómez-Santos; Rafael Romero-Becerra; et al. (Nature Communications)
Abstract Obesity poses a global health challenge, demanding a deeper understanding of adipose tissue (AT) and its mitochondria. This study describes the role of the mitochondrial protein Methylation-controlled J protein (MCJ/DnaJC15) in orchestrating brown adipose tissue (BAT) thermogenesis. Here we show how MCJ expression decreases during obesity, as evident in human and mouse adipose tissue samples. MCJKO mice, even without UCP1, a fundamental thermogenic protein, exhibit elevated BAT thermogenesis. Electron microscopy unveils changes in mitochondrial morphology resembling BAT activation. Proteomic analysis confirms these findings and suggests involvement of the eIF2α mediated stress response. The pivotal role of eIF2α is scrutinized by in vivo CRISPR deletion of eIF2α in MCJKO mice, abrogating thermogenesis. These findings uncover the importance of MCJ as a regulator of BAT thermogenesis, presenting it as a promising target for obesity therapy.